2005
DOI: 10.1103/physrevb.71.184410
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and magnetocaloric properties and the magnetic phase diagram of single-crystal dysprosium

Abstract: Magnetic materials exhibiting magnetic phase transitions simultaneously with structural rearrangements of their crystalline lattices hold promise for numerous practical applications including magnetic refrigeration, magnetomechanical devices, and sensors. We undertook a detailed study of a single crystal of dysprosium metal, which is a classical example of a system where magnetic and crystallographic sublattices can be either coupled or decoupled from one another. Magnetocaloric effect, magnetization, ac magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 31 publications
(29 reference statements)
6
38
0
1
Order By: Relevance
“…Three transitions are observed: at ∼ 30 K, ∼ 45 K, and ∼ 110 K. The sharp peak at T C ≅ 30 K corresponds to the first order AFM-FM transition. A similar transition (sharp peak) is observed in the C P data of pure Er at T C ≅ 19 K. 33,34 In pure Dy, the first order C P peak is observed at T C ≅ 90 K. 3,7 The transition observed at ∼45 K resembles the anomaly observed in the C P of pure Er at T N ⊥ ≅ 53 K, where the CAM structure transforms into the APD magnetic structure. 3,33 No such anomaly is observed in pure Dy.…”
Section: Properties Along the [0001] Direction (Or C Axis)supporting
confidence: 53%
See 4 more Smart Citations
“…Three transitions are observed: at ∼ 30 K, ∼ 45 K, and ∼ 110 K. The sharp peak at T C ≅ 30 K corresponds to the first order AFM-FM transition. A similar transition (sharp peak) is observed in the C P data of pure Er at T C ≅ 19 K. 33,34 In pure Dy, the first order C P peak is observed at T C ≅ 90 K. 3,7 The transition observed at ∼45 K resembles the anomaly observed in the C P of pure Er at T N ⊥ ≅ 53 K, where the CAM structure transforms into the APD magnetic structure. 3,33 No such anomaly is observed in pure Dy.…”
Section: Properties Along the [0001] Direction (Or C Axis)supporting
confidence: 53%
“…The AFM order changes over to the FM one below T C ≅ 90 K. When a magnetic field is applied anywhere between T C and 135 K, the magnetic structure of Dy changes from a helix AFM to FM. 7,17 Between 135 K and 180 K, the AFM-FM transition is separated by an intermediate fan magnetic phase, which is stable between ∼7 and ∼25 kOe. 7,17 Low temperature x-ray diffraction studies of single crystal Dy showed that the FM transition at 90 K is accompanied by a structural transition from hcp to a distorted orthorhombic structure along with significant discontinuities in lattice parameters.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations